Foundations of entrepreneurship and economic development - Harper, David A. (London ; New York : Routledge, 2003)
Deals with entrepreneurship in all its aspects. It considers the economic, psychological, political, legal and cultural dimensions of entrepreneurship from a market-process perspective and analyses why some people are quicker than others in discovering profit opportunities.
Includes bibliographical references (p. [241]-267) and index.
oif 30/04/15
Loan
Keywords: Entrepreneurship; New business enterprises; Economic development